An Assessment of Gross State Domestic Product at Constant (2011-12) Prices in India from 2011 to 2017 - SRINIVASAN Dr. S (Journal of Economic and Social Development (Varaždin), 2019)
Contextual Assess the Gross State Domestic Product (GSDP) at Constant (2011-12) Prices in India and states and union territories from 2011 to 2017. Methods Technical analyses of percentage growth rate of GSDP at constant (2011-12) prices over previous year 2011-12 and regression applied to the assessment of GSDP are carried out. Results It helps to take remedial measure to increase the GSDP and formulate policies for improvement of the state/union territories of India.